The Mudharabah Savings Demand among the Member of Islamic Financial Service Cooperatives in Bogor - Aisyah, Muniaty; Umiyati, U. (Ekonomi Syariah IAIN Kudus, 2018)
The Islamic Financial Service Cooperative or Baitul Maal wa Tamwil (BMT) is potential to become an effective economic driving forcefor micro and small businesses in Indonesia due to its ability to raise public funds. Nevertheless, BMT experiences many obstacles, one of which in marketing. It needs a better understanding of its member behavior that could predict the demand of its products and services. This research aimed to examine the members’ demand on Mudharabah savings of BMT in Bogor, by using the multiple linear regression analysis. The finding shows that the service quality does not influence the members’ decision to use Mudharabah savings because the services provided by BMT are below of members’ expectation, thus, they need to enhance their service quality. This research sheds the light on some strategies in order to improve service quality of BMT in Indonesia.